Internet censorship detected in Bangladesh (Bangladesh) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Bangladesh. Data sourced from CensoredPlanet.
Censorship Incident ID: BD-2026-0127. Severity: warning. Confidence: 65%